The news of the Bradwell v. Illinois, determined by the Supreme Court of the United States in 1873, with the persistent lack of equality in the work of women (separation, segmentation, prohibition) in its hundred and fiftieth anniversary - Vizcaíno Ramos, Iván (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2023)
This work examines the timeliness of the words contained in a landmark 1873 United States Supreme Court decision rejecting a woman’s claim to practice law, to the effect that women were unsuitable for many professions because of «the natural and proper timidity and delicacy which belongs to the female sex». On the occasion of the one hundred and fiftieth anniversary of the decision in question, it is analyzed to what extent expressions such as the aforementioned, or similar expressions, have been repeated until they have become a historical constant. And to what extent the persistent lack of equality for women in the workplace may be perpetuated in the future, especially if certain professions or activities (such as that of conducting an orchestra) continue to be classified as dangerous, presumably only for women, who will then continue to need protection.